Research of Flow Characteristics Hybrid Model of Steam Turbine Stage Based on the Improved PSO Algorithm - Zhao Ming; Yan Zhengbo; Zhou Liukun; Wang Huijie; Xu Xiaogang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Power station steam turbine stage flow characteristics show the Corresponding relationship between pressure and flow rate, which is the important research foundation for analysis of steam turbine performance and the further optimization analysis of unit. Based on strict theory analysis, this article obtained two important key characteristic coefficients such as the capacity of flow coefficient and the level of group critical pressure ratio which mainly influenced the turbine characteristics. And then the secondary flow calculation model was imposed combining with the massive actual data, adapting the method of improved PSO algorithm. The practical results show that, the obtained model not only ensured good regularity and ductility, but also has higher calculation precision. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3501